KEBIJAKAN MANAJEMEN PENDIDIKAN AGAMA ISLAM PADA SMA 1 SIMANJAYA : DOI: https://doi.org/10.37850/cendekia.v12i1.100 - Nur Zaini (Fakultas Agama Islam Universitas Billfath, 2020)
This study aims to reveal (1) the application of Islamic education programs and organizing, the implementation of policies and the implementation of educational programs, the evaluation process and the level of educational success, the supporting and inhibiting factors for the development of Islamic education management in SMA 1 Simanjaya Siman Lamongan. This research is qualitative research, using a rationalistic approach. The tool obtains data by using methods of observation, literature study, and interviews for processing data by using descriptive analysis. In general, the application of Islamic education management in SMA 1 Simanjaya Siman Lamongan has been carried out, the functions of education management have been carried out correctly. The implementation of Islamic education policy in SMA 1 Simanjaya Siman Lamongan has been directed at efforts to improve the quality of the school's image, and the level of success tends to increase. Supporting factors for the implementation of Islamic education management in SMA 1 Simanjaya Siman Lamongan is an institutional factor that has a juridical basis as a reference for organizing education, KBK curriculum which is the core of the education process, Location of SMA 1 Simanjaya Siman Lamongan SMA 1 Simanjaya Siman Lamongan which is a strength for SMA 1 Simanjaya Siman Lamongan, Human Resources (HR) or educational staff which is a critical element in the development of educational institutions and the support of parents of students who are built through the School Committee. Whereas the obstacle in implementing Islamic education management in SMA 1 Simanjaya Siman Lamongan is the perception of the community who still think that Private Schools are places of education that are not yet of quality, do not however have modern educational facilities and infrastructure, the quality of inputs is still low and sources of funding are still minimal.